The health care services quality impact on patient loyalty mediating by patient satisfaction in Jordan - Alkawamleh, Salahaldeen; Ghazali, Puspa liza; Afthanorhan , Wan Mohamad Asyraf Bin Wan; Rahim, Mohamad Zulkifli Bin Abdul (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose: This study seeks to highlight the significance of patient satisfaction in the connection between patient loyalty and Services Quality. Design / Methodology: A total of 357 patients from 11 government hospitals in Jordan were asked to complete questionnaires. The collected data was analyzed using Structural Equation Modeling (SEM). Findings: Findings that providers in government hospital in Jordan are attempting to deliver well improved healthcare services to their customers. Results confirmed health services to build satisfaction and loyalty among patients. Health services quality including the factors such as reliability, assurance and tangibility are positively related with patient loyalty which is mediated through patient satisfaction.